A Study Evaluating the Bidirectional Relationship Between Inflammatory Bowel Disease and Self-reported Non-celiac Gluten Sensitivity. Issue 4 (April 2015) - Aziz, Imran; Branchi, Federica; Pearson, Katherine; Priest, Josephine; Sanders, David S.
Abstract : Background: Non-celiac gluten sensitivity and the associated use of a gluten-free diet (GFD) are perceived to belong to the spectrum of irritable bowel syndrome (IBS). However, recent reports suggest substantial use of a GFD in inflammatory bowel disease (IBD). We assessed the bidirectional relationship between IBD and self-reported non-celiac gluten sensitivity (SR-NCGS). Methods: A cross-sectional questionnaire screened for SR-NCGS and the use of a GFD in 4 groups: ulcerative colitis (n = 75), Crohn's disease (n = 70), IBS (n = 59), and dyspeptic controls (n = 109). We also assessed diagnostic outcomes for IBD in 200 patients presenting with SR-NCGS. Results: The prevalence of SR-NCGS was 42.4% (n = 25/59) for IBS, followed by 27.6% (n = 40/145) for IBD, and least among dyspeptic controls at 17.4% (n = 19/109); P = 0.015. The current use of a GFD was 11.9% (n = 7/59) for IBS, 6.2% (n = 9/145) for IBD, and 0.9% (1/109) for dyspeptic controls; P = 0.02. No differences were established between ulcerative colitis and Crohn's disease. However, Crohn's disease patients with SR-NCGS were significantly more likely to have stricturing disease (40.9% versus 18.9%, P = 0.046), and higher mean Crohn's Disease Activity Index score (228.1 versus 133.3, P = 0.002), than those without SR-NCGS. Analysis of 200 cases presenting with SR-NCGS suggested that 98.5% (n = 197) could be dietary-related IBS. However, 1.5% (n = 3) were found to have IBD; such patients had associated alarm symptoms, and/or abnormal blood parameters, prompting colonic investigations. Conclusions: SR-NCGS is not only exclusive to IBS but also associated with IBD, where its presence may be reflecting severe or stricturing disease. Randomized studies are required to further delineate the nature of this relationship and clarify whether a GFD is a valuable dietetic intervention in selected IBD patients. Abstract : Article first published online 25 February 2015.